2007
DOI: 10.1002/jcb.21417
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and genetic mechanisms contribute to telomerase inhibition by EGCG

Abstract: The ends of human chromosomes are protected from the degradation associated with cell division by 15-20 kb long segments of hexameric repeats of 5'-TTAGGG-3' termed telomeres. In normal cells telomeres lose up to 300 bp of DNA per cell division that ultimately leads to senescence; however, most cancer cells bypass this lifespan restriction through the expression of telomerase. hTERT, the catalytic subunit essential for the proper function of telomerase, has been shown to be expressed in approximately 90% of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(173 citation statements)
references
References 33 publications
9
163
1
Order By: Relevance
“…In 2008, over 12 million new cancer cases were diagnosed worldwide, breast cancer being one of the most frequently diagnosed in women, and the one characterized with the highest mortality rate [10]. However, a large body of data exists on the influence of polyphenols of plant origin on breast cancer [11][12][13][14]. For instance, an extract from the fruit of Terminalia chebula Retz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, over 12 million new cancer cases were diagnosed worldwide, breast cancer being one of the most frequently diagnosed in women, and the one characterized with the highest mortality rate [10]. However, a large body of data exists on the influence of polyphenols of plant origin on breast cancer [11][12][13][14]. For instance, an extract from the fruit of Terminalia chebula Retz.…”
Section: Introductionmentioning
confidence: 99%
“…(yellow myrobalan or chebulic myrobalan) effectively inhibits the proliferation of murine and human mammary gland cancer cells (S115 and MCF-7, respectively) [11]. Epigallocatechin gallate (EGCG), the main phenolic constituent of green tea whose antiproliferative activity towards cancer cells is the most widely reported among polyphenols, also inhibits the growth of MCF-7 cells [12]. Genistein, a soy isoflavone, was found to cause G2/M cell cycle arrest in MDA-MB-231 and MCF-7 mammary gland cancer cell lines [13].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of telomerase has also been shown after EGCG treatment. In this study, EGCG downregulated hTERT expression in MCF-7 human breast cancer cells, largely as a result of TERT promoter demethylation and ablated histone H3 Lys9 acetylation (Berletch et al, 2008).…”
Section: Epigenetic Dietmentioning
confidence: 65%
“…Furthermore, EGCG (0-100 µM) dose-dependently inhibited OVCAR-3 cell migration. The protein expression levels of MMP-2, but not MMP-9, were dose-dependently decreased following treatment with EGCG (0-100 µM) for 48 h; leading to inhibited OVCAR-3 cell proliferation and migration, potentially mediated via the activation of p38 MAPK and downregulation of the protein expression of MMP-2 .It has been reported that EGCG can induce apoptosis in breast cancer cells, and EGCG can target cancer cells through a variety of mechanisms, including decreasing expression of hTERT, the major catalytic subunit of telomerase (Berletch et al, 2008).…”
Section: Ovarian and Cervical Cancermentioning
confidence: 99%